Risiko Produksi Usahatani Padi Organik di Kecamatan Cihaurbeuti Kabupaten Ciamis - Ramdani, Ari Kurniawan; Suminartika, Eti; Charina, Anne (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This study aims to analyze the production risks faced by organic rice farmers in Cihaurbeuti Sub-district, Ciamis Regency. Organic rice farming in this area faces various challenges, including unpredictable climate change, pest and disease attacks, and limited access to quality organic inputs. This research employs a descriptive quantitative method with data collection through direct interviews with organic rice farmers. The results indicate that the variability in organic rice production is very high, with a coefficient of variation of 106.9%, indicating significant fluctuations in crop yields. To mitigate these risks, it is recommended to implement sustainable farming practices, use modern agricultural technology, and adopt agricultural insurance systems.